Social cognition - Pennington, Donald C. (Routledge, 2000)
Annotation Social Cognition looks at the way in which humans interpret, analyze and remember information about the social world. Topics include: attribution, social schemas and social representations, prejudice and discrimination.
Keywords: Social perception.; Social Perception; Perception sociale.; PSYCHOLOGY -- Social Psychology.; Social perception